2012
DOI: 10.1002/wdev.100
|View full text |Cite
|
Sign up to set email alerts
|

Retinal differentiation in Drosophila

Abstract: Drosophila eye development has been extensively studied, due to the ease of genetic screens for mutations disrupting this process. The eye imaginal disc is specified during embryonic and larval development by the Pax6 homolog Eyeless and a network of downstream transcription factors. Expression of these factors is regulated by signaling molecules and also indirectly by growth of the eye disc. Differentiation of photoreceptor clusters initiates in the third larval instar at the posterior of the eye disc and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 148 publications
5
113
0
Order By: Relevance
“…As a result, the posterior regions contain more mature ommatidial units than the anterior regions. The process appears similar to the extensively studied morphogenesis of the adult Drosophila eye (Treisman, 2013). During ommatidial differentiation, Aaop7 is briefly expressed in ommatidial units at the anterior edge of developing compound eye.…”
Section: Discussionsupporting
confidence: 56%
“…As a result, the posterior regions contain more mature ommatidial units than the anterior regions. The process appears similar to the extensively studied morphogenesis of the adult Drosophila eye (Treisman, 2013). During ommatidial differentiation, Aaop7 is briefly expressed in ommatidial units at the anterior edge of developing compound eye.…”
Section: Discussionsupporting
confidence: 56%
“…In this sense, we were curious to see whether Ato regulates glass, both because of its expression pattern right before the onset of Glass expression and because of the importance of Ato to induce neural cell fate in PR precursors ( Fig. S11; Jarman et al, 1994;Aerts et al, 2010;Treisman, 2013). However, we found that Glass is still expressed in ato mutant clones in the third instar eye disc, suggesting that both Glass and Ato work in parallel, but independently (Fig.…”
Section: Ectopic Expression Of Glass and Hazy Drives Expression Of Prmentioning
confidence: 91%
“…At this stage, the RDN member So directly activates the proneural gene ato at the morphogenetic furrow, and Ato induces the formation of PR precursors. Although extensive information is available on the activation of ato, and on how Ato specifies PR precursors to become neurons (Zhang et al, 2006;Tanaka-Matakatsu and Du, 2008;Aerts et al, 2010;Treisman, 2013;Jusiak et al, 2014), little is known about how these neurons become mature PRs. We propose that activation of glass by either the RDN or Ato should be a key step in this process.…”
Section: Ectopic Expression Of Glass and Hazy Drives Expression Of Prmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoreceptor differentiation in the developing eye initiates in the morphogenetic furrow (Treisman, 2013). Anterior to the morphogenetic furrow, cells are undifferentiated and asynchronously proliferating.…”
Section: Introductionmentioning
confidence: 99%